Blood Type and their Relationship with Motivational Behaviours - Shyam B. R.; Aithal P. S. (International Journal of Health Sciences and Pharmacy (IJHSP), 2022)
Purpose: All people, including you and me, have motivational behaviors, and every individual comes up with different factors to influence their motivational behavior. It is what makes us the person we are. Our motivational behaviors take care of our behavior, thinking ability, emotions, thoughts, and even individual feelings, even at their unconscious levels. Such that, the mentioned things will always help in forecasting the future and also their behavioral changes in different situations. Many of the earlier studies have proved that there is no correlation between motivation levels of the individual through their blood group, but the concept remains more popular in all dimensions. Objective: The researchers have set the following primary objective and the current study investigates a broad research question to identify whether blood type has a relationship with motivational behaviors. Methodology: The study is based on secondary evidence. In this regard, various libraries were visited and some online journals were also reviewed in this direction. Findings/Result: Researchers have found that blood type does have a relationship with personality and behaviors in countries where belief in the blood type personality theory is strong. This study concluded that people changed their personality to fit their blood type instead of in a self-fulfilling prophecy. Thus, blood type does have a relationship with motivational behaviors like motivation is an internal process, the anatomy of motivation, motivational traits, character motivation, and neuro motivation, intrinsic and extrinsic &major determinants of motivation. Research Implications: Motivational behaviors need to be tackled with the weapon of trend motivational techniques i.e., beyond monetary compensation for which the blood type and their relationship with motivational behaviors help a lot. Originality/Value: Other researchers have found that blood type does have a relationship with personality and behaviors. Similarly, blood type affects motivational behaviors. In countries like Japan, Korea, Asia, etc., where belief in the blood type personality theory is strong. This study concluded that people changed their motivation & personalities to fit their blood type instead of in a self-fulfilling prophecy. In this way, it is similar to the use of astrological signs, which is also popular in Japan. Paper Type: The present study made an attempt to identify whether blood type has a relationship with motivation. The study is based on secondary evidence.